2015
DOI: 10.1186/s13618-015-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy ameliorates TNBS-induced acute distal colitis in rats

Abstract: BackgroundThis study investigated the therapeutic effects of hyperbaric oxygen in experimental acute distal colitis focusing on its effect on the production of pro-inflammatory cytokines, nitric oxide and hypoxia-inducible factor 1alpha.MethodsColitis was induced with a rectal infusion of 150 mg/kg of TNBS under anesthesia with Ketamine (50 mg/kg) and Xylazine (10 mg/kg). Control animals received only rectal saline. After colitis induction, animals were subjected to two sessions of hyperbaric oxygen and were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
20
0
3
Order By: Relevance
“…These findings are consistent to the previous study of ours and the others in adult rats (Huang et al, 2013;Yang et al, 2015). Among a collection of therapeutic strategies against neurological diseases (Dock et al, 2015;Li et al, 2015;Lioutas et al, 2015;Merali et al, 2015;Ploughman et al, 2015;Qi et al, 2015;Reuter et al, 2015;Schlunk et al, 2015;Soliman et al, 2015;Zhu et al, 2015), medical gas regimens have been extensively explored with the advantage of administration feasibility (Harch, 2015;Herrera et al, 2015;Hu et al, 2015;Ichihara et al, 2015;Langston and Toombs, 2015;Miller et al, 2015;Parra et al, 2015;Stoller, 2015;Weaver and Liu, 2015;Yan et al, 2015). Emerging evidence has shown HBO induces neuroprotection against a variety of neurological disorders including severe TBI (Huang and Obenaus, 2011).…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent to the previous study of ours and the others in adult rats (Huang et al, 2013;Yang et al, 2015). Among a collection of therapeutic strategies against neurological diseases (Dock et al, 2015;Li et al, 2015;Lioutas et al, 2015;Merali et al, 2015;Ploughman et al, 2015;Qi et al, 2015;Reuter et al, 2015;Schlunk et al, 2015;Soliman et al, 2015;Zhu et al, 2015), medical gas regimens have been extensively explored with the advantage of administration feasibility (Harch, 2015;Herrera et al, 2015;Hu et al, 2015;Ichihara et al, 2015;Langston and Toombs, 2015;Miller et al, 2015;Parra et al, 2015;Stoller, 2015;Weaver and Liu, 2015;Yan et al, 2015). Emerging evidence has shown HBO induces neuroprotection against a variety of neurological disorders including severe TBI (Huang and Obenaus, 2011).…”
Section: Resultssupporting
confidence: 92%
“…Since this landmark publication in Nature Medicine, research on the molecular hydrogen medicine has blossomed worldwide. Emerging evidence has demonstrated the pleiotropic therapeutic effects of molecular hydrogen in a variety of animal disease models and some human patients (Huang et al, 2010;Ohta, 2011;Dixon et al, 2013;Ishibashi et al, 2015;Kurokawa et al, 2015), which are comparable to what have been found with other traditional therapeutic gases regimens including hyperbaric/normobaric oxygen (Harch, 2015;Hu et al, 2015;Parra et al, 2015;Stoller, 2015;Weaver and Liu, 2015;Yan et al, 2015) and hyrogen sulfide (H 2 S) (Herrera et al, 2015;Langston and Toombs, 2015). H 2 is now considered as a signaling gaseous molecule with physiological functions similar to that of nitric oxide (NO), carbon monoxide (CO), and H 2 S (Kajimura et al, 2012).…”
Section: Introductionmentioning
confidence: 77%
“…The classical concept of the plasma membranes is extremely permeable to gases, which has been extended to the solubility-diffusion mechanism for the gas transport across plasma membrane, including O 2 and CO 2 (Finkelstein, 1976;Harch, 2015;Katz et al, 2015;Langston and Toombs, 2015;Parra et al, 2015;Stoller, 2015). It is generally believed that both O 2 and CO 2 molecules are transport across the plasma membrane through diffusion.…”
Section: For the Pursuit Of Oxygen And Carbon Dioxide Channels In Mitmentioning
confidence: 99%